The Sale of Human Organs in the Law of Donation and Transplantation of Human Body Organs in Kurdistan Region of Iraq: A Jurisprudential Evaluative Study - Ismael, Ardawan Mustafa; ismail, Rebaz sdiq (Journal of Tikrit University for Humanities, 2023)
Allah made human being as His successor on earth, and has honored him with the best honor in the various phases of his life. Selling a person or one of his organs contradicts this honor, and a person is not a commodity until he is sold and bought in the market. Therefore, Islam has prohibited all financial interests if the purpose of it is to sell a person or one of his organs. A set of international laws have been issued prohibiting the sale of human organs, including the law of human organ donation and transplantation in Iraqi Kurdistan, where this law was exposed to the issue of selling human organs. This paper aims to clarify the similarities and differences between the law of Kurdistan of Iraq and jurisprudence by adopting an analytical and evaluative approach, the paper concluded with a set of findings and recommendations.